How do you transform parametric equations into Cartesian form: x= 3 + 2 cost and y= 1 + 5sint?
graph{25x^2+4y^2-150x-8y+129=0 [-7.295, 12.705, -3.92, 6.08]}
By signing up, you agree to our Terms of Service and Privacy Policy
To transform parametric equations into Cartesian form, eliminate the parameter by solving for it in one of the equations and substituting it into the other equation. For ( x = 3 + 2\cos(t) ) and ( y = 1 + 5\sin(t) ), square both equations and rearrange to solve for (\cos(t)) and (\sin(t)) respectively. Then, substitute these expressions into one of the original equations to obtain the Cartesian equation.
( x = 3 + 2\cos(t) )
( x - 3 = 2\cos(t) )
( \cos(t) = \frac{x - 3}{2} )
( y = 1 + 5\sin(t) )
( y - 1 = 5\sin(t) )
( \sin(t) = \frac{y - 1}{5} )
Substitute (\cos(t) = \frac{x - 3}{2}) into ( \sin^2(t) + \cos^2(t) = 1) to eliminate the parameter.
( \sin^2(t) + \left(\frac{x - 3}{2}\right)^2 = 1 )
( \sin^2(t) + \frac{(x - 3)^2}{4} = 1 )
( \sin^2(t) = 1 - \frac{(x - 3)^2}{4} )
( \sin(t) = \pm \sqrt{1 - \frac{(x - 3)^2}{4}} )
Substitute ( \sin(t) = \frac{y - 1}{5} ) into the equation above.
( \frac{y - 1}{5} = \pm \sqrt{1 - \frac{(x - 3)^2}{4}} )
Solve for ( y ).
( y - 1 = \pm 5\sqrt{1 - \frac{(x - 3)^2}{4}} )
( y = 1 \pm 5\sqrt{1 - \frac{(x - 3)^2}{4}} )
By signing up, you agree to our Terms of Service and Privacy Policy
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
- How do you differentiate the following parametric equation: # x(t)=t-(t+1)e^t, y(t)= t^2-e^(t-1) #?
- How do you differentiate the following parametric equation: # x(t)=-te^t-2t, y(t)= 3t^3-4t #?
- How do you differentiate the following parametric equation: # x(t)=1/t, y(t)=lnt #?
- How do you find the vector equation and the parametric equations of the line that passes through the points A (3, 4) and B (5, 5)?
- For #f(t)= (sint,cost)# what is the distance between #f(pi/4)# and #f(pi)#?
- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7